Race, ethnicity and social stratification in three Windward Islands - Albuquerque, Klaus de (1999)
Examines the social and economic characteristics associated with race and ethnicity in three relatively under-researched majority African-Caribbean societies - Dominica, St. Lucia and St. Vincent - selected because of their similarities in size, history and socio-economic structure.